2005
DOI: 10.1111/j.1600-0633.2005.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and food resource use of perch and roach in a deep mesotrophic reservoir: enough space to avoid competition?

Abstract: Habitat and food resource use of perch and roach in a deep mesotrophic reservoir: enough space to avoid competition?Un resumen en espan˜ol se incluye detra´s del texto principal de este artı´culo. Kahl U, Radke RJ. Habitat and food resource use of perch and roach in a deep mesotrophic reservoir: enough space to avoid competition? Ecology of Freshwater Fish 2006: 15: 48-56. Ó Blackwell Munksgaard, 2005Abstract -The aim of this study was to test assumptions about the interaction of perch (Perca fluviatilis L.) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 47 publications
5
46
1
Order By: Relevance
“…In artificially destratified, deep reservoirs fish inhabited the whole volume (Prchalová et al 2006). In the sharply stratified Římov Reservoir the highest fry density was usually observed in the surface layer as has also been observed for adult fish in other stratified lakes and reservoirs Järvalt et al 2005;Kahl & Radke 2006;Prchalová et al 2008).…”
Section: General Distribution Of Fry In the Reservoirsupporting
confidence: 71%
See 1 more Smart Citation
“…In artificially destratified, deep reservoirs fish inhabited the whole volume (Prchalová et al 2006). In the sharply stratified Římov Reservoir the highest fry density was usually observed in the surface layer as has also been observed for adult fish in other stratified lakes and reservoirs Järvalt et al 2005;Kahl & Radke 2006;Prchalová et al 2008).…”
Section: General Distribution Of Fry In the Reservoirsupporting
confidence: 71%
“…Roach in the Římov Reservoir thus preferred the surface water where the temperature was highest. The segregation of perch and roach along the temperature gradient in the pelagic zone was probably a result of selecting their optimal temperatures with respect to species-specific foraging efficiency and growth (Kahl & Radke 2006).…”
Section: Distribution Of Different Fry Species In the Reservoirmentioning
confidence: 99%
“…However, in situ studies of the vertical distribution of different species in lake with fishing nets or by echo sounding often show vertical spatial segregation, in which roach are positioned in higher water layers than those occupied by perch (Persson, 1986;Horppila et al, 2000). Kahl and Radke (2006) and Vasek et al (2009) found that roach occurs during the day in the layer just above the thermocline (3 to 4.5 m) and occupies the upper epilimnion (0−3 m) at night, whereas perch occupy the lower epilimnion and upper metalimnion (1.5−6 m). In Lake Annecy, the epilimnion is much thicker, approximately 15 m, and the water transparency is always greater than 6 m (as measured by a Secchi disk).…”
Section: > What δ 18 O Tell About the Thermal Distribution Of Lake Anmentioning
confidence: 99%
“…In our case, the two species are predator (P. fluviatilis) and prey (R. rutilus) (Turesson and Brönmark 2004) and they school in different aggregations. Furthermore, these two species exhibit different behaviors (Eklöv and Persson 1995;Kahl and Radke 2006) and physiology (Thorpe 1977). Eklöv and Persson (1995) have shown that juvenile roach form denser schools in the presence of predators, and have a higher swimming speed in the open water than juvenile perch.…”
Section: Discussionmentioning
confidence: 99%